Use of Antihypertensive Drugs During Preeclampsia - Odigboegwu, Obinnaya; Pan, Lu J.; Chatterjee, Piyali (Frontiers in Cardiovascular Medicine, 2018)
Treatment of pregnancy-related hypertensive disorders, such as preeclampsia (PE), remain a challenging problem in obstetrics. Typically, aggressive antihypertensive drug treatment options are avoided to prevent pharmacological-induced hypotension. Another major concern of administering antihypertensive drugs during pregnancy is possible adverse fetal outcome. In addition, management of hypertension during pregnancy in chronic hypertensive patients or in patients with prior kidney problems are carefully considered. Recent studies suggest that PE patients are at increased cardiovascular risk postpartum. Therefore, these patients need to be monitored postpartum for the subsequent development of other cardiovascular diseases. In this review article, we review the antihypertensive drugs currently being used to treat patients with PE and the advantages or disadvantages of using these drugs during pregnancy.